Perencanaan Strategis Sekolah Berdasar Rapor Pendidikan: Studi Kualitatif di SMPN 3 Tengaran Semarang - Lusi Kurniasari; Ida Solowati; Hanum Fajar Susanti; Desy Dwi Widarwati; Ngurah Ayu Nyoman (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study aims to analyze the strategic planning process based on the 2024 Education Report Card at SMPN 3 Tengaran, Semarang Regency. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings reveal that the school utilized Report Card data to develop strategic planning using SWOT analysis and the Reflect-Improve framework. Strengths include teacher competence and leadership support, while weaknesses involve disparities in student achievement and limited ICT integration. Opportunities are optimized through supportive policies and technological advancements, whereas threats stem from curriculum changes and socioeconomic inequality. The reflection stage led to prioritized programs focused on improving literacy, numeracy, and character development. The success of implementation is strongly influenced by the principal’s leadership and needs-based teacher training. This study confirms that data-driven strategic planning contributes to improving educational quality and can serve as a model for other schools.